2012
DOI: 10.1371/journal.pone.0033366
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Intravital Method to Evaluate Cerebral Vasospasm in Rat Models of Subarachnoid Hemorrhage: A Study with Synchrotron Radiation Angiography

Abstract: Precise in vivo evaluation of cerebral vasospasm caused by subarachnoid hemorrhage has remained a critical but unsolved issue in experimental small animal models. In this study, we used synchrotron radiation angiography to study the vasospasm of anterior circulation arteries in two subarachnoid hemorrhage models in rats. Synchrotron radiation angiography, laser Doppler flowmetry-cerebral blood flow measurement, [125I]N-isopropyl-p-iodoamphetamine cerebral blood flow measurement and terminal examinations were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 46 publications
1
49
0
Order By: Relevance
“…On theoretical grounds, other analyses independently predict an exponent of −0.375 for shear stress scaling in mammalian aortas, but indicate that this value is not necessarily universal for all arteries (Weinberg and Ethier, 2007). We estimated the scaling of shear stress for the internal carotid artery from measured data from 70 kg humans (this study) and 375 g rats (Cai et al, 2012) using the shear stress equation and literature values. Blood flow rate in one internal carotid artery is taken as 3.83 cm 3 s −1 in humans (Boysen et al, 1970) and 0.028 cm 3 s −1 in rats (mean of four studies: Nakao et al, 2001;Ohno et al, 1979;Sakurada et al, 1978;Takagi et al, 1987).…”
Section: Shear Stress (τ)mentioning
confidence: 99%
See 1 more Smart Citation
“…On theoretical grounds, other analyses independently predict an exponent of −0.375 for shear stress scaling in mammalian aortas, but indicate that this value is not necessarily universal for all arteries (Weinberg and Ethier, 2007). We estimated the scaling of shear stress for the internal carotid artery from measured data from 70 kg humans (this study) and 375 g rats (Cai et al, 2012) using the shear stress equation and literature values. Blood flow rate in one internal carotid artery is taken as 3.83 cm 3 s −1 in humans (Boysen et al, 1970) and 0.028 cm 3 s −1 in rats (mean of four studies: Nakao et al, 2001;Ohno et al, 1979;Sakurada et al, 1978;Takagi et al, 1987).…”
Section: Shear Stress (τ)mentioning
confidence: 99%
“…Blood flow rate in one internal carotid artery is taken as 3.83 cm 3 s −1 in humans (Boysen et al, 1970) and 0.028 cm 3 s −1 in rats (mean of four studies: Nakao et al, 2001;Ohno et al, 1979;Sakurada et al, 1978;Takagi et al, 1987). ICA lumen radius is taken as 0.221 cm in humans (mean of three studies: Kane et al, 1996;Krejza et al, 2006;Porsche et al, 2002) and 0.0304 in rats (Cai et al, 2012). Blood viscosity is considered invariant at 0.04 dyne s cm −1 (SchmidSchönbein et al, 1969).…”
Section: Shear Stress (τ)mentioning
confidence: 99%
“…4). The 3-day time point was based on available data regarding the development of vasospasm [1,23,24,25]. Subsequently, animals were sacrificed and vessels were harvested.…”
Section: Resultsmentioning
confidence: 99%
“…Previous rodent studies showed that this model mimics SAH [16], including the induction of cerebral vasospasm [23,37]. This model is considered to be relatively well developed and is broadly accepted.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it provides an important means of assessing blood flow dynamics in tumors. With appropriate consideration of radiation exposure, it is now possible to observe alterations in vascular morphology and intratumoral micro-hemodynamics during tumor progression sequentially over time Cai, Sun et al, 2012). Further studies are needed to develop new markers of abnormal tumor microvessels.…”
Section: Discussionmentioning
confidence: 99%